1006. Demographic, Clinical, Microbiological Characteristics and Outcome of Patients Admitted to the Emek Medical Center with Blood Stream Infection Acquired in LTCF: A 5-Year Surveillance. (26th November 2018) - Almog, Moty; Yanovskay, Anna; Edelstein, Hana; Colodner, Raul; Schwartz, Naama; Chazan, Bibiana
Abstract: Background: Residents from long-term care facilities (LTCF) hospitalized with an acute infectious disease are challenging in terms of diagnosis and treatment, considering atypical clinical presentation are high rate of resistant bacteria, . This study aimed to Characterize patients with LTCF acquired bacteremia (LTCF-B), epidemiology of blood cultures (BC) and potential risk for mortality. Methods: A retrospective study of LTCF residents hospitalized with LTCF-B. Demographic, clinical and laboratory data were collected and analyzed using SPSS 22 and SAS. Results: One hundred seventy-seven LTCF residents hospitalized in internal wards were included, mean age 81.6 years, mostly completely dependent, 54.8% were males. Most frequent diagnoses was urinary tract infection (UTI), second by respiratory tract infections. Half were hospitalized during prior 6 months, one-third had a permanent indwelling urinary catheter. On admission, 70% had WBC blood count >10, 000 cells/mL. The following pathogens were isolated from BC: Gram-negative enterobacteriaceae (70%): E. coli were 40% and Gram-positive cocci (21%): S. aureus 5.08% (55.5% of them MRSA). Extended-spectrum-β-lactamase (ESBL) producing enterobacteriaceae were in 47.1% BC, clearly document increase during the years, 26% (2010)–63% (2014). Absolute majority of enterobacteriaceae were sensitive to carbapenems and amikacin, half were resistant to gentamycin, second- and third-generation cephalosporins and quinolones. Inappropriate empiric antimicrobial therapy was given to 46.8% of patients with ESBL-producing enterobacteriaceae ( P < 0.001). Mortality rates were 21.5% in-hospital and 46.3% day-90 post discharge. Variables associated with mortality: initial diagnosis of skin and soft-tissue infections (SSTI) (OR = 14.44), inappropriate empiric antibiotic (OR = 5.038), high level of urea (OR = 1.017), and nasogastric tube (OR = 4.966). UTI (OR = 0.316) was a protective factor. Conclusion: Diagnosis of SSTI, high urea levels, nasogastric tube, and inappropriate empiric antibiotic were associated with in-hospital mortality. The notable increased rate of ESBL-producing enterobacteriaceae should alert physicians to be aware of local microbial resistance profile, especially among LTCFs patients. Disclosures: All authors: No reported disclosures.